Does Learning Culture Impact Directly or Indirectly on Work Engagement in the Indonesia Oil Palm Industry? - Saputra, Nopriadi; ., . (International Journal of Engineering and Technology, 2018)
Indonesia oil palm industry (IOPI) has become rapid growth industry and plays strategic role in global and domestic socio-economy. IOPI is facing many social, environmental and managerial issues. The employees with high score on learning agility and work engagement become the requirement. And developing organizational culture that promotes and supports learning process is a must for palm oil company in Indonesia. This study aims to explore the impact of learning culture on learning agility and work engagement. Does learning culture impact directly or indirectly on work engagement? The study was conducted on 73 respondents who are senior staffs, supervisors and junior managers from 28 companies in IOPI. Smart-PLS application was used for statistical data analysis in this study. The result explained that learning culture impacts indirectly (with path coefficient 0.142) and directly (with path coefficient 0.248) on work engagement. The development of organizational learning culture also impact directly on learning agility (with path coefficient 0.276). It is a strategic initiative for dealing with current and future business challenges.